Educación y calidad - Aguirre Ledesma, Lía (2010)
The notion of quality in the "quality in education" debate  should not be understood as an equivalent to client satisfaction as in the productivity approach which applies the scheme agent/client/product. In the education field, quality is much more complex and ideological, and is attached to the development expectations of many different social sectors. In this regard, this article focuses on the importance of putting "education situations" in context so as to identify sorne aspects that should be consider in the implementation of quality education.